Do exchange rates absorb demand shocks at the ZLB? - Mathias Hoffmann; Patrick Hürtgen (Deutsche Bundesbank, 2021)
According to the two-country full information New Keynesian model with flexible exchange rates, the real exchange rate appreciates in response to an asymmetric negative demand shock at the zero lower bound (ZLB) and exacerbates the adverse macroeconomic effects. This finding requires inflation expectations to adjust counterfactually large. When modeling inflation expectations consistent with survey expectations using imperfect information, we find that exchange rates can absorb demand shocks at the ZLB. In sharp contrast to the full information model: (i) A negative demand shock concentrated in the home country causes a real exchange rate depreciation that partially absorbs the demand shock. (ii) A VAR with an identified demand shock via sign restrictions is consistent with a real exchange rate depreciation at the ZLB. (iii) When the ZLB is binding in the home country, it is optimal for the foreign policymaker to reduce rather than increase foreign interest rates. (iv) Forward guidance that reveals the true state of the economy exacerbates the negative output gap in the two countries.
Keywords: F33; E31; E32; 330; monetary policy; inflation expectations; imperfect information; real exchange rates